2018
DOI: 10.1007/s12182-018-0288-0
|View full text |Cite
|
Sign up to set email alerts
|

Emission and performance study emulsified orange peel oil biodiesel in an aspirated research engine

Abstract: This study paves the way on reducing smoke emission and NO x emissions of research diesel engine by detailing the effect of water addition in biodiesel. Fuel samples were prepared with different concentrations of water in orange peel oil biodiesel (94% waste orange peel oil biodiesel + 4% water + 2% Span 80 (WOPOBDE1) and 90% waste orange peel oil biodiesel + 8% water + 2% Span 80 (WOPOBDE2). Span 80 was employed as a nonionic surfactant, which emulsifies water in biodiesel. Experimental results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(16 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Fuel with lower viscosity improves the atomization process and enhances combustion efficiency and BTE. The obtained results agree with numerous other experimental works performed on alcohol/biodiesel/diesel blends (Senthilkumar et al 2018;Venu and Madhavan 2016;Siva et al 2018;Rajesh Kumar and Saravanan 2015). Figure 8 illustrates the change in BSFC for B10P90, B20P80, P100 and diesel.…”
Section: Brake Thermal Efficiencysupporting
confidence: 89%
“…Fuel with lower viscosity improves the atomization process and enhances combustion efficiency and BTE. The obtained results agree with numerous other experimental works performed on alcohol/biodiesel/diesel blends (Senthilkumar et al 2018;Venu and Madhavan 2016;Siva et al 2018;Rajesh Kumar and Saravanan 2015). Figure 8 illustrates the change in BSFC for B10P90, B20P80, P100 and diesel.…”
Section: Brake Thermal Efficiencysupporting
confidence: 89%
“…Figure 8 depicts the variation of percentage of CO emission with increasing BP output for all the tested fuels and the graph conveys that CO emissions increased with increasing Brake load, but with a steep rise in 3.3-4.4 kW range. There are some research works in the literature whose results found in agreement with the case [40][41][42][43][44]. From the Fig.…”
Section: Co Emissionsupporting
confidence: 83%
“…Referring to Figure 4, in general, the torques of diesel engine with B30 fuel were lower than the torque of diesel engines with pure diesel fuel. It was not surprising since biodiesel fuel had a lower heating value to diesel oil as reported by Abed et al (2018) and Siva et al (2019). This work revealed that the rising of transesterification temperature led to the higher torque of the diesel engine.…”
Section: Resultssupporting
confidence: 58%